The effectiveness of living well multicultural‐lifestyle management program among ethnic populations in Queensland, Australia. (27th February 2020) - Gallegos, Danielle; Do, Hong; To, Quyen Gia; Vo, Brenda; Goris, Janny; Alraman, Hana
Abstract: Issue: Some migrant groups have higher risks of deaths and chronic diseases due to barriers associated with socioeconomic disadvantage, social isolation, racism, language, poor access to health services and low levels of health literacy. However, few culturally tailored interventions have targeted ethnic groups in Australia. This study evaluated the effectiveness of the Living Well Multicultural‐Lifestyle Management Program (LWM‐LMP) in Queensland, Australia. Methods: The LWM‐LMP was originally co‐designed with the targeted communities. Participants aged ≥18 years were eligible to participate without a fee. The evaluation was a quasi‐experimental design without a control group, with data collected at baseline, the end of the programme and after‐programme follow‐up at week 14. The programme lasted 8 weeks with one group‐based session of 120 minutes delivered each week in local community venues. Each session also included time to undertake physical activity (PA). Eating and PA behaviours were self‐reported. Weight, height, waist circumference and blood pressure were measured using standard protocols. Results: Participants were more likely to consume ≥2 servings of fruit/day, five servings of vegetable/day, low‐fat milk, processed meat, fast food, hot chips/fries, salty snacks, sweet snacks, sweet beverages less than once per week and meet the PA recommendation of ≥150 minutes/wk ( P < .001) at week 8. Weight, BMI, waist circumference, waist‐to‐height ratio and blood pressure were also improved at week 8. Many of the changes were sustained at week 14. Conclusions: The LWM‐LMP was effective in improving participants' lifestyle behaviours and cardiometabolic indicators. So what: Engaging targeted communities in designing interventions focussed on healthy personal behaviours helps with delivery and implementation. Behavioural interventions should be culturally tailored to increase their effectiveness.